The Reliability of the Progression of Autonomies Scale Applied on Acquired Brain Injured Patients - Arcuri, Francesco; Cortese, Maria Daniela; Riganello, Francesco; Lucca, Lucia Francesca; Serra, Sebastiano; Mazzucchi, Anna; Cerasa, Antonio; Tonin, Paolo (Frontiers in Neurology, 2019)
The Progression of Autonomies Scale (PAS) is a behavioral scale useful to assess the autonomy levels in acquired brain-injured patients. It provides a broad profile, assessing different domains of human activities ranging from personal, domestic, and extradomestic autonomies. This cross-sectional study is aimed at evaluating the reliability of this scale on a large cohort of acquired brain injury (ABI) patients. Fifty-one ABI patients (49% traumatic, 33.3% hemorrhagic, 17.7% other etiologies), hospitalized in the S. Anna Institute of Crotone, Italy (mean age male 46.08 ± 14.53 and mean age female patients 43.2 ± 11.3) were recruited. We found a high level of reliability of the scale, with a coefficient at the inter-rater agreement between substantial (0.61 ≤ k ≤ 0.8) and almost perfect (0.81 ≤ k ≤ 1), and almost perfect at the test-retest (intra-rater). We confirm that the PAS is a well-structured tool for the assessment of the autonomy levels in brain-injured patients. These findings encourage the application of this scale in the clinical practice of rehabilitation unit to design a tailored rehabilitation treatment on real goals and to monitor the generalization of the recovered abilities to the daily routine activities.